2023
DOI: 10.3390/molecules28155754
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic Silver Nanoparticles/Mg-Al Layered Double Hydroxides with Peroxidase-like Activity for Mercury Detection and Antibacterial Activity

Masira I. Chamanmalik,
Arnet Maria Antony,
C. V. Yelamaggad
et al.

Abstract: Over the past decade, the attention of researchers has been drawn to materials with enzyme-like properties to substitute natural enzymes. The ability of nanomaterials to mimic enzymes makes them excellent enzyme mimics; nevertheless, there is a wide berth for improving their activity and providing a platform to heighten their potential. Herein, we report a green and facile route for Tectona grandis leaves extract-assisted synthesis of silver nanoparticles (Ag NPs) decorated on Mg-Al layered double hydroxides (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 57 publications
2
15
0
Order By: Relevance
“…Presently observe, the FNPs can withstand both types of bacteria with an inhibition zone of 10 mm after 24 hours of growth at 37 °C. This demonstrates that FNPs can enhance the antimicrobial activity of FSHT samples [55,57] . The FSHT samples also against the above two species of bacteria with high value of inhibition zone.…”
Section: Resultsmentioning
confidence: 61%
See 1 more Smart Citation
“…Presently observe, the FNPs can withstand both types of bacteria with an inhibition zone of 10 mm after 24 hours of growth at 37 °C. This demonstrates that FNPs can enhance the antimicrobial activity of FSHT samples [55,57] . The FSHT samples also against the above two species of bacteria with high value of inhibition zone.…”
Section: Resultsmentioning
confidence: 61%
“…The FSHT samples also against the above two species of bacteria with high value of inhibition zone. Along with recovery enhancement, the inclusion of FNPs improved antibacterial properties of the FSHT samples [57] . As a result, the FSHT particles aspired to have strong antibacterial and self‐cleaning membrane capabilities when exposed to sunshine.…”
Section: Resultsmentioning
confidence: 98%
“…To determine the effect of reaction parameters such as variation in pH of acetate buffer, catalyst loading, and concentrations of H 2 O 2 and OPD on the peroxidase-like activity of the BC-AHE@Pd nanocatalyst, the oxidation was carried out under varying reaction conditions. The peroxidase-like activity is related to the pH according to the pH-dependent studies, as well as the concentrations of substrates and nanocatalysts [ 48 , 49 ]. The superlative activity of the BC-AHE@Pd nanocatalyst was obtained at pH 4 ( Figure 8 a), with OPD (100 μM) and H 2 O 2 (40 mM) in the presence of 0.31 mol% Pd of the BC-AHE@Pd nanocatalyst.…”
Section: Resultsmentioning
confidence: 99%
“…The appearance of these extract peaks in the IR spectra leads to suggestion that organic substances also contribute to the modification of the HT surface in the HT-AgNPs samples, and they potentially act as a stabilization agent for AgNPs. [41] This highlights the distinction between the use of a chemical reducing agent and a plant extract reducing agent. Ballarin et al reported that the FTIR spectra of ZnAl-AgNPs were similar to that of raw ZnAl HT when using glucose or sodium citrate as reducing agents to convert Ag(I) to AgNPs.…”
Section: Ir Spectramentioning
confidence: 99%
“…They were applied as sensors for mercury detection. [41] From the above literature, it can be seen that Psidium guajava leaf extract is an efficient reducing agent for converting Ag(I) ions to AgNPs. However, the study on the 'green' synthesis of AgNPs on HT particles using Psidium guajava leaf extract as a reducing agent has still been limited.…”
Section: Introductionmentioning
confidence: 99%